Peningkatan Literasi Pada Anak-Anak Dan Remaja Melalui Pojok Baca Di Desa Mekarjaya Kecamatan Compreng - Nurul Alda; Fitria Zulfa; Ilham Agustian; Anisa Mutiara (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The Literacy Movement is an important initiative in fostering reading habits and motivation in society, especially in children and teenagers, with the main aim being to foster good character. However, the implementation of the literacy movement in Mekarjaya Compreng Village is still not optimal, because there are still many children and teenagers who are less enthusiastic about reading. Therefore, Student KKN STAI Darussalam Kunir participated in carrying out a literacy movement to increase interest in reading among the children and teenagers of the village.The aim of this movement is not only to increase interest in reading, but also to expand knowledge and improve effective communication skills, both in the community and at school. By establishing a reading corner as a library in Mekarjaya Village, it is hoped that people will be encouraged to love readingThe method used in this activity is a qualitative method which includes pre-implementation, implementation and post-implementation stages. Observations were carried out to analyze the conditions and needs of local communities, with the results leading to the development of reading corners, especially for children and teenagers.Through these steps, it is hoped that the literacy movement can run smoothly and have a positive impact in increasing interest in reading and effective communication skills in Mekarjaya Compreng Village.